A perfect match? Exploring the interplay between public service motivation and conscientiousness in predicting public organizational outcomes. Issue 3 (4th May 2022) - Lauritzen, Heidi Hesselberg; Pedersen, Mogens Jin
Abstract: How may we understand the relationships between public service motivation (PSM), personality traits, and public organizational outcomes? Do organizational outcomes relate to interaction associations between PSM and personality traits? Using a mix of survey data and administrative data from a sample of nursing home care workers in Denmark ( n = 427), this article explores the interplay between PSM and the personality trait of conscientiousness in relation to two organizational outcomes: performance and short-run absenteeism. We find that PSM is associated with higher performance and less absenteeism and that conscientiousness is a significant moderator of both relationships—although in distinct ways. The association between PSM and less absenteeism is greater at higher levels of conscientiousness. In contrast, the positive association between PSM and performance attenuates to zero at high levels of conscientiousness.